Notes for the history of Obstetrics and Gynecology in Peru - Álvarez-Carrasco, Ricardo (2021)
Gynecology and Obstetrics has a history of very ancient roots in Peru, rich in transcendent milestones, thanks to the intelligence, talent and tenacity of numerous doctors who contributed to form the scientific and academic body that today represents an important part of Peruvian medicine. The purpose of this article is to make a synthesis of that interesting and profitable history for the memory of Peruvians in general and of the national medical order in particular.